Large pneumatocele as a rare complication in SARS-CoV-2 infection of the lung - Gillissen, Adrian; Zimmermann, Thomas; Clasen, Stephan (Pneumologie, 2022)
In this paper, we present a case of SARS-CoV2-Virus a non-vaccinated 54-year-old male admitted with COVID-19 pneumonia and respiratory insufficiency requiring high-flow oxygen supplementation. CT-scan of the lung revealed multifocal bilateral ground-glass opacities and – as a rare complication – a large pneumatocele in the middle of the posterior part of the left lower lobe. In order to treat the pneumatocele, a 10 F was placed into the cavity. The resulting pneumothorax was successfully treated with a 20 F chest tube over a 9-day period. The pneumatocele shrank only slightly. This case demonstrates a unique radiologic finding in COVID-19, which is likely the result of severe inflammation secondary to SARS-CoV-2 including an unfruitful attempt at depressurisation.
Keywords: Pneumatozele; Pneumothorax; SARS-CoV-2; Pneumonie